Hubungan Kuasa Komunikasi Panggung Penyanyi Dangdut - Fitriya, Alvi; Dwiningtyas, Hapsari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
Power is an important component of social relation which is used by individuals to maintain their position in social arena. Environment can be the determinant factor for an individual to show their power in social arena. The aim of the study is to find out power relations of stage communication among orkes melayu dangdut show’s agents using ethnography as the type of study. Theories used in this study include Agent and Structure Theory which is a derivation of Habitual and Arena Concept, and is explaining that agent structure is interconnected in social practices among economic, cultural, social, and symbolic capitals. It is added with Theory of Power which explains that power is an innate value in every individual in the structure of power relation hierarchy. The result of the study shows that stage communication happened during dangdut show performed by orkes melayu consists of show agents including singers, music players, tenants, MCs, audiences, and producers are divided into two domains, they are front stage and back stage. In every scope of domain, each dangdut show’s agent has capital which is used to create a new capital of each show agent. The capital achieved among music players, MCs, and producers is economic capital. Then, the capital achieved among singers, tenants and audiences is symbolic capital. The symbolic capital becomes a driving factor for show agents to get power relations in a social relation in a dangdut show, However in this research, symbolic capital which own by the singer become weak by the power because there is subjection. So based on that the singer has negative image. Therefore, each agent of dangdut show should maintain their main capital in social arena to be able to survive in a social arena of dangdut show and use it as a bridge and a way to gain power in every social relation